Improved rates of exclusive breastfeeding at 14 weeks of age in KwaZulu Natal, South Africa: what are the challenges now? - C. Horwood; L. Haskins; IM Engebretsen; S. Phakathi; C. Connolly; A. Coutsoudis; L. Spies (BMC, 2018)
Abstract Background Increasing the rate of exclusive breastfeeding (EBF) to 50% in the first six months of life is one of six major global targets set by the United Nations Decade of Nutrition, and is essential to achieve the sustainable development goals to eradicate hunger and end malnutrition by 2030. Methods A survey using multistage random sampling design included 99 primary health care (PHC) clinics in all 11 districts in KwaZulu-Natal (KZN). All mothers and caregivers of infants 14 weeks of age attending the clinics in the study period were requested to participate in a structured interview to explore feeding practices since birth. As non-maternal caregivers may not have detailed knowledge of feeding practices, they provided limited information about current feeding practices. Respondents who consistently reported giving no other food or fluids except breastmilk since birth were classified as practising exclusive breastfeeding (EBF), and those who were currently breastfeeding but had given other food or fluids since birth were categorised as practising mixed breastfeeding (MBF). Results A total of 4172 interviews were conducted with mothers and caregivers of 14 week old infants. Among mothers 49.8% were EBF, 23.1% were MBF and 27.0% were not breastfeeding. Among non-maternal caregivers 11.8% reported EBF, 23.4% MBF and 62.3% were not giving breastmilk. Higher education (OR 0.6, 95% CI 0.4-0.8) and being in the highest socio-economic tertile (OR 0.7, 95% CI 0.6-0.9) were risk factors for not practising EBF, while returning to work (OR 0.3, 95% CI 0.2-0.3) or school (OR 0.2 95% CI, 0.1-0.3) was associated with less EBF. HIV-positive mothers were more likely to have never started breastfeeding (OR 3.6, 95% CI 2.7-4.8). However, they were similar in having stopped breastfeeding by 14 weeks (OR 1.1, 95% CI 0.9-1.4) compared to HIV-negative mothers, and, they had similar rates of EBF at 14 weeks of age (OR 1.0, 95% CI 0.9-1.3). Conclusions Estimates of breastfeeding practices at 14 weeks in KZN are higher than previously shown. However, particular challenges that should be addressed if international targets for EBF are to be achieved include improving breastfeeding practices of HIV positive mothers and supporting all mothers, particularly working or schooling mothers to continue giving breastmilk while they are away from their children.